New nests of Zethus reveal unexpected architecture variation in the olmecus species group (Hymenoptera, Vespidae) - Lopes, Rogério Botion [UNESP]; Melo, Gabriel A.R. (FapUNIFESP (SciELO), 2025)
Zethus Fabricius is the largest known genus in Vespidae, but very little is known about their nesting behavior. Belonging to the Z. olmecus species group, Zethus miniatus is widely known for its subsocial behavior, where females build together aerial nests comprised of a cluster of several cells. Nests of closely related species of the same species group, Z. notatus, Z. schadei and Z. thoracicus, collected in the Amazon basin, are here described and illustrated. Nests of Z. notatus and Z. thoracicus reveal architectures very distinct from those of Z. miniatus. Although examined nests are all aerial and comprised of at least four cells, the orientation and maceration of vegetable matter vary among these species. Finally, notes on social behavior and progressive provisioning of Z. schadei and Z. thoracicus are provided.
Keywords: Communal nesting; Nest structure; Zethus (Zethoides)